Differences in Sexual Function Between Trimesters During Pregnancy: An Observational Study - Soysal, Sunullah; Sarioz, Abdullah; Kilincdemir Turgut, Umran; Anik Ilhan, Gokce; Arman, Yusuf; Yildizhan, Begum; Pekin, Tanju (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: The aim of this study was to evaluate differences in sexual function between trimesters, and factors (in addition to pregnancy) that influence sexual function during pregnancy. STUDY DESIGN: This observational study was conducted at a tertiary referral center with 372 pregnant women. Seventy-two of the women did not complete the questionnaire (rejections or missing data) and the overall response rate was 80.6%. Among the remaining women, 43 of them excluded due to depression. Beck Depression Inventory was used to evaluate depression. Index of female sexual function questionnaire was used to assess sexual function. Index of female sexual function had a total and six sub-domain scores which assess the quality and frequency of sexual intercourse, desire, overall satisfaction, ability to achieve orgasm, and degree of clitoral sensation (c.sensation). RESULTS: Total index of female sexual function and quality, satisfaction, orgasm, and c.sensation sub-domain scores were lowest in the third trimester. Older age, lower level of education, and lower level of income negatively affected total index of female sexual function scores. Quality scores were lowest in older women and women with lower education. Frequency scores were highest during the second trimester. Desire scores were highest in women aged between 18 and 25 years, in women who were newly married (1-3 years), and during the second trimester. Satisfaction scores were lowest in women older than 35 years, and highest in newly married women. Orgasm scores were highest in women aged 18-25 years, in newly married women. CONCLUSIONS: Sexual function in women during the third trimester of pregnancy is generally affected negatively.